Industrial verification of energy saving for the single-tier cylinder based paper drying process. (1st March 2019) - Chen, Xiaobin; Man, Yi; Zheng, Qifu; Hu, Yusha; Li, Jigeng; Hong, Mengna
Abstract: The paper drying process has the highest level of energy consumption in the pulp and paper production process. Analysis and optimization of the energy system during the paper drying process is critical for improving the energy efficiency of the entire paper mill. In the existing model for the paper drying process, the solution requires accurate boundary conditions such as the air temperature and humidity of the pocket area and the cylinder surface temperature, which are very difficult to obtain in the papermaking process. This can result in significant deviations between the model solution and the actual production process. This paper focuses on the single-tier dryer cylinder-based paper drying process that has been widely used with high-speed papermaking machines in recent years. A mathematical model is proposed based on real-time data. The verification via industrial production demonstrates that the proposed model is reliable for the paper drying process. Based on the simulation results, two optimization operations have been proposed. The energy consumption decreases from 1.51 t steam/t paper to 1.44 t steam/t paper, 4.6% of the steam and 1.26 × 10 6 RMB can be saved for a medium-scale paper mill with the annual production capacity of 10 5 t paper. Highlights: Mathematical model for the single-tier cylinder based paper drying process is proposed. Both the steam-condensate system and the paper drying process are considered. The simulation results are verified by the industrial data from a papermaking enterprise.